Telenovela brasileira, censura e sexualidade: uma história de amor e ódio - Melo, Ana Cláudia da Cruz (2018)
This doctoral thesis presents the results of research on how soap operas (telenovelas) have established a field of germination of moral problems in Brazil. The research stops between 1964, the year in which the Military Regime begins in the country, and 2015, when there is the exhibition of Babilônia (International title: Ambitious Women), soap opera (telenovela) produced and broadcast by Rede Globo, and marked by intense controversy due to the approach of plot with two lesbian characters. It is based on three fronts of analysis. The first examines speeches and statements of a set of documents that were processed in the governmental sphere until 1988, based on the 1967 Constitution, which provided for censorship of "externalizations contrary to morality and good manners". About this documentation, it focuses on true discourses concerning sex and about homosexuality and the way soap operas have affected people. The second front of analysis, under the same perspective as the first one, dwells on the letters published in the section of the reader of Jornal do Brasil, between 1978 and 2000. The year 1978 was chosen because it marked the beginning of the process of reopening democratic Brazil. The year 2000 marked the turning point in the soap opera‘s timetable, that is, when the main plots left the celebrated eight o'clock time to occupy the one at 9 o'clock, which came to be considered "noble." The third front of analysis was in the posts about Babilônia on the page of Rede Globo, on Facebook. We looked for, to verify how the soap opera continued, in these times of digital social networks, mobilizing discourses of sex, feelings and emotions. For this investigation, we bring theorists - their concepts, reflections, and propositions - as good companions of a long journey. Kilpp (2003) and Machado (2000) to delineate the concept of Brazilian soap opera (telenovela) beyond television. Foucault (1979, 1984a, 1984b, 1988, 2008) when he talks about the history of sexuality and at the same time about how to study the emergency conditions of discourses of a given epoch. Eribon (2008), Butler (2002, 2003, 2009), Lauretis (1992, 1994) and Preciado (2017) give us elements to question the controversies surrounding the theme of homosexuality in soap operas (telenovelas). De Latour (2012) his recommendations about how to follow the controversies. And from Spinoza (2014) the ways to think about affection, affects and, above all, the passions. Research that, among its results, presents the soap opera (telenovela) as a social technology that has in sex one of its main instruments and supports. As such, it demanded attention, care and controls to defend "morality and good manners". Between 1964 and 2015, there were innumerable forms of control beginning with institutional censorship, during the military regime, through ordinances, regulations, social mobilizations, up to the indicative classifications adopted today. This study is justified to the extent that it hopes to have contributed to the construction of knowledge whether in the problematization of human sexuality or in the history of Brazilian audiovisual, in perspective of the soap operas (telenovelas)